New Trends in Yorùbá Personal Names among Yorùbá Christians - ̀Ikọ̀tún Reuben Olúwáfẹ́mi (Linguistik Online, 2014)
In this paper, we examine new trends in Yorùbá personal names that are first names among Yorùbá Christians. The data used include data drawn from previous studies on Yorùbá personal names, the lists of names of the candidates of the Joint Admissions and Matriculation Board of Nigeria the lists of staff of three Nigerian universities, some attendance registers of pupils in nursery, primary and secondary schools as well as participant observation. We show that the European or established Churches and the newly founded autochthonous Nigerian Churches have different influences on Yorùbá naming system and tradition-based Yorùbá personal or first names. We also indicate that, at present, there is a complete cultural shift from the use of tradition-based Yorùbá personal names as first names to the use of biblical or Christian names and that this new dimension is as a result of the influence of western culture or civilization and the newly founded churches in Nigeria. We further show that the activities that are shrouded in fanaticism, flavours, modernisation and especially names that endear the Nigerian believers to one another are meant to prove that the newly founded autochthonous Nigerian churches understand the Bible teachings better than the European churches and that name modification or name change is inevitable when there is acculturation.